PS01.048: LAPAROSCOPIC ANTIREFLUX SURGERY IN MORBIDLY OBESE PATIENTS. (14th September 2018) - Migaczewski, Marcin; Rubinkiewicz, Mateusz; Pędziwiatr, Michał; Major, Piotr; Dworak, Jadwiga; Natkaniec, Michał; Budzyński, Andrzej
Abstract: Background: Laparoscopic Roux-en-Y gastric bypass (LRYGB) has been proved to be effective bariatric procedure for the treatment of morbidly obese patients with gastroesophageal reflux disease (GERD). In contrast, the indication for laparoscopic sleeve gastrectomy (LSG) in these group of patients is still not clear. LSG with simultaneous crural repair it can be a new, safe and effective therapautic approach. Methods: A total of 60 obese patients with GERD operated on in 2016–2018 were included in the study. 20 patients were qualified for LRYBG. In the rest LSG was performed, of which half with simultaneous crural repair. Results: GERD symptoms complete control was observed in 18/20 (90%) patients after LRYGB and 17/20 (85%) after LSG with simultaneous crural repair. The same effect occurred only in 8/20 patients direct after simple LSG. 'De novo' GERD symptoms developed in 10% of the patients undergoing alone LSG during 12 months follow up. Conclusion: Laparoscopic Roux-en-Y gastric bypass (LRYGB) is still effective bariatric procedure for the treatment of morbidly obese patients with gastroesophageal reflux disease (GERD). Doubts remain in the situation of young patients without diabetes. If we additionally deal with a large hiatal hernia, the qualification for LRYGB remains debatable. In this situation, it is worth considering LSG. Simple sleeve gastrectomy not only does not guarantee a good anti-reflux effect, but it can also produce de-novo GERD. Laparoscopic simultanous crurolasty in the time of LSG, represents a valuable option for the treatment of morbid obesity with gastroesophageal reflux disease Disclosure: All authors have declared no conflicts of interest.